Effectiveness of Reminiscence Therapy and Deep Breath Relaxation Therapy on Stress Levels of Elderly During the Covid-19 Pandemic - Lale Wisnu Andrayani; GA Sri Puja Warnis Wijayanti; Desty Emilyani; Qibithia Maria Malik (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2023)
In the COVID-19 pandemic, the triggering factor for stress among the elderlies is that they are afraid of contracting COVID-19, becoming a source of transmission, and dying from Covid-19. In fact, the level of risk of transmission and death in elderly patients is higher than in younger. This study aims determine the effectiveness of reminiscence therapy and deep breathing relaxation therapy on reducing stress levels in the elderly during the Covid-19 pandemic. This study used a quasi-experimental pre-posttest method. The sample was 32 elderlies who experience moderate and mild stress in Terong Tawah Village, chosen using the purposive sampling method. Data collection used the DASS questionnaire, analyzed using the paired T-test and the independent t-test. Results showed the average stress level before reminiscence therapy was 20,06 and after therapy was 14.06. Whereas, the average stress level before deep breathing relaxation therapy was 20.25 and after therapy was 17.06. There was an effect of reminiscence therapy and deep breathing relaxation therapy the stress levels of the elderly with ρ value = 0.00. However, there was no significant difference between the effectiveness of reminiscence therapy and that of deep breathing relaxation therapy. (p-value = 0.022, α = 0.05). It can be concluded that reminiscence therapy and deep breathing relaxation therapy are both effective in reducing stress levels in the elderly. Health workers can provide education about reminiscence therapy by involving the family and deep breathing relaxation for the elderly as an alternative therapy to reduce stress levels.